ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) PADA BANK BUMN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2013-2020 - Imelda Talahatu (Jurnal Administrasi Terapan, 2023)
Analysis of Bank Soundness Level Using the RGEC Method in BUMN COMMERCIAL BANKS Listed on the Indonesia Stock Exchange for the 2013-2020 period.This study aims to determine the soundness of state-owned commercial banks for the 2013-2020 period in terms of the overall aspects of Risk profile, Good Corporate Governance (GCG), Earnings, Capital, and RGEC (Risk profile, GCG, Earnings, and Capital). This type of research is descriptive research with research subjects in the form of state-owned commercial banks listed on the Indonesia Stock Exchange in 2013-2020. Data were obtained through documentation techniques. The data analysis technique used is the soundness analysis of a bank using a risk approach (Risk-based Bank Rating) with the scope of the assessment covering RGEC factors.The results of the study show that during the 2013-2020 period: The RGEC aspect as a whole is in a Composite Rating 2, which is very healthy with a score of 80%.Keywords: Bank Soundness Level, BUMN Commercial Banks, RGEC Method